Manuel Сastells’ concept of the power of communication in the scientific discourse of digital sociology - M. V. Kibakin; M. M. Kryukova (Цифровая социология)
The article describes the methodological, methodic and socio-project aspects of the views of the modern sociologist and political scientist M. Castells in the framework of a discursive analysis of the possibilities of their use in the further institutionalization of digital sociology, as a relatively autonomous set of scientific data of sociology. The author considers literary sources related to the scientific work of M. Castells, methodological tools of discursive analysis and databases. The paper describes theoretical approaches to the study of the concept of the power of communication in ontological and socio-cultural contexts, as well as the characteristics of the author’s empirical sociological research in the framework of disclosing the logical and semantic components of the concept under consideration. Based on the discursive analysis, the author reveals structural, functional, procedural, organizational and managerial components of the theoretical views of the scientist, which help to clarify the object-subject sphere and the methodological arsenal of sociological research in the field of information and communication network “Internet”. The article considers the scientific approaches of the scientist to clarify the concept of “power” by explaining the role and place of actors in it, as well as use by them of social networks for their influence. The author highlights separately the scientist`s disclosure of the “network society” concept, which determines the network structure of connections based on the activation of information. The paper describes the features of the scientific method of M. Castells, associated with the postulation of the thesis of the regularity of the continuous replacement of scientific concepts in the knowledge of power relations and communications, the importance of flexibility and changing the angle of view of the scientist to solve specific research problems. The author emphasizes the interdisciplinary nature of the scientific methodology, method and socio-project approaches of the scientist. The study gives the directions of implementation of scientific developments of M. Castells in digital sociology, substantiates socio-project ways of increasing the positive potential of Internet communications in the context of digital society development.